Numerical study of heat transfer performance of suspension of nanofluids in heat exchanger tube / Rosmawati Mat Jihin - Rosmawati, Mat Jihin (2013)
This study was focus on the flow separation phenomena of annular passage which appears in a number of flow situations. It practically observed to cause recirculation flows that will affect the amount of heat transfer rate in several engineering application. The primary aim of this study is to identify the performance of three type of nanofluids : Al2O3 at 0.5%, 1% and 2% volume fractions and CuO and TiO2 at 2% concentration over the base fluid water. The model considered is an annular passage with sudden expansion, having a constant step height, s=13.5mm for Al2O3 and TiO2 and various step height , s=6mm, 13.5mm and 18.5mm for CuO uniformly heated with constant heat flux, q=49050 W/m2. This geometries is evaluated and simulated using CFD software package ANSYS 14.0. The solver used standard k-ε turbulence model in calculating the solution for the flow field given by Reynolds number 17050, 302720, 39992 and 44545 for both uniform flow and fully developed turbulent flow. The investigation shows that the increase of Reynolds number will reduce the surface temperature at the reattachment zone. The lowest temperature will occur at this area and shows the location of reattachment point. The surface temperature will increase gradually with the pipe distance for all the nanofluids applied.